Statistical Optimization of Green Fluorescent Protein Production from Escherichia coli BL21(DE3) - Chew, Few Ne; Tan, Siang Wen; Boo, Chern Huey; Tey, Ti Beng (Taylor & Francis Group, 2012)
An optimized cultivation condition is needed to maximize the functional green fluorescent protein (GFP) production. Six process variables (agitation rate, temperature, initial medium pH, concentration of inducer, time of induction, and inoculum density) were screened using the fractional factorial design. Three variables (agitation rate, temperature, and time of induction) exerted significant effects on functional GFP production in E. coli shake flask cultivation and were optimized subsequently using the Box-Behnken design. An agitation rate of 206 rpm at 31°C and induction of the protein expression when the cell density (OD(600nm)) reaches 1.04 could enhance the yield of functional GFP production from 0.025 g/L to 0.241 g/L, which is about ninefold higher than the unoptimized conditions. Unoptimized cultivation conditions resulted in protein aggregation and hence reduced the quantity of functional GFP. The model and regression equation based on the shake flask cultivation could be applied to a 2-L bioreactor for maximum functional GFP production.